Inovasi Digital dalam Manajemen Persampahan: Perancangan Prototype E-Sampah sebagai Solusi untuk Mengoptimalkan Pengelolaan Sampah di Kota Gorontalo - Bau, Rahmat Taufik R.L; A., Hermila; Ahaliki, Budiyanto; Engelan, Adnan (International Journal of Computer and Information System (IJCIS), 2023)
Gorontalo City is the largest contributor of waste in Gorontalo Province. Waste production in Gorontalo City increases to 140 tonnes per day based on data from the National Waste Management Information System. One of the things that caused the waste problem in Gorontalo to become more severe is the difficulty in transporting waste due to the limited transport fleet. Furthermore, the Waste Management Reuse, Reduce, and Recycle (TPS3R) personnel in several sub-districts are no longer functioning. This article details the emergence of innovative waste management applications, providing a new paradigm for cities to become digitally connected hygiene centers. The app not only revolutionizes the way waste is perceived but also offers smart solutions to optimize waste management efficiently. With a modern and progressive approach, the app creates an interactive experience for the people of Gorontalo to manage their waste. Through smart center and route mapping features, the app empowers citizens to actively contribute to keeping the city clean. In addition, the integrated information system enables quick and informed decision-making for authorities, creating responsive and effective waste management. The research conclusion confirms that the design of E-Sampah with a focus on the centre point and route of waste collection by waste officers can provide a modern and accessible solution for the people of Gorontalo. The results of the System Usability Scale (SUS) assessment with a score of 80.5 indicate that this waste management information system received a positive response from users. This prototype is expected to change mindsets and shape behaviors that support sustainable waste management.